(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
The article deals with the inclusion of sports in modern socio-cultural processes, the problem of transnational commercialization of sports. The process of turning sports into a modern commodity, into a social service that freely crosses the borders of sovereign states is shown